Eine Kartei deutscher Ortsnamen mit Rückwärts-alphabet - Rösch, S. (ERDKUNDE, 1958)
The purpose of this article is to inform those interested about the establishment of a card index of all German place names. Its basis is the “Ortsnummernverzeichnis des deutschen Reiches (edition B, complete list edited by the A. W. V., Leipzig, 1928, together with seven supplements, 1929?1935), which means that the catalogue contains all names as they existed at that period and within the then boundaries of Germany. In contrast to the former work, which comprises an alphabetical as well as a numbered part, this index, consisting of about 66,000 cards, is arranged in alphabetical order according to the last letter of the name, and then within each of these groups according to the last but one letter and so forth. Each place name is recorded on a separate card on which the place numbers of all places of the same name are also given. This arrangement facilitates the tackling of a number of problems in a new way. On the one hand it makes it easier to find the old forms of place names since experience shows that in those cases where place names have changed fairly often it have mostly been the first parts of the names which suffered and less frequently the last: e. g. Biebrich and Wiesbaden-Biiebrich, Wimpfen and Bad Wimp fen, Ebersbach and Strassebersbach or Bergebersbach, etc.; this aspect was the reason for establishing the index in the way chosen. On the other hand, this arrangement makes the catalogue an almost inexhaustible source for toponymists and geographers who can now easily trace all place names with the same terminal syllables (like -husen, -rode, -deich, -torf, -moor, -by, etc.), and investigate their regional distribution. For a study like that the place numbers are a further valuable help. In the article a few examples of that kind of work are given and results presented descriptively and diagrammatically. In addition a few statistical considerations are appended which resulted from the counting out of the cards. The card index is housed in 30 boxes and is at present in the historical archive of the city of Wetzlar. Research workers are invited to use it on the premises or to write there for information; in the latter case they are asked to enclose return postage and to limit their enquiries to points that can be answered briefly, since lack of time and personnel make it impossible to deal with anything more complicated.